2021
DOI: 10.3390/ijms22157766
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Carbonic Anhydrase Genes in Lotus japonicus and Their Potential Roles in Symbiotic Nitrogen Fixation

Abstract: Carbonic anhydrase (CA) plays a vital role in photosynthetic tissues of higher plants, whereas its non-photosynthetic role in the symbiotic root nodule was rarely characterized. In this study, 13 CA genes were identified in the model legume Lotus japonicus by comparison with Arabidopsis CA genes. Using qPCR and promoter-reporter fusion methods, three previously identified nodule-enhanced CA genes (LjαCA2, LjαCA6, and LjβCA1) have been further characterized, which exhibit different spatiotemporal expression pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Extensive research has been conducted in recent decades to explore the functions of CAs in various physiological processes across photosynthetic organisms. Although genome-wide identification of CA gene families has been achieved in different species using whole-genome sequencing technologies (Fabre et al, 2007, Smith and Ferry, 2000, Tiwari et al, 2005, DiMario et al, 2017, Feng et al, 2015, Wang et al, 2021, Carbonic anhydrase (CA) is a universally occurring enzyme found in various organisms, playing a crucial role in facilitating the interconversion of CO 2 and HCO 3 À (bicarbonate ion) (Sanogo and Zhang, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research has been conducted in recent decades to explore the functions of CAs in various physiological processes across photosynthetic organisms. Although genome-wide identification of CA gene families has been achieved in different species using whole-genome sequencing technologies (Fabre et al, 2007, Smith and Ferry, 2000, Tiwari et al, 2005, DiMario et al, 2017, Feng et al, 2015, Wang et al, 2021, Carbonic anhydrase (CA) is a universally occurring enzyme found in various organisms, playing a crucial role in facilitating the interconversion of CO 2 and HCO 3 À (bicarbonate ion) (Sanogo and Zhang, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Expression yields were not reported. CAs from higher plants were mainly expressed in the original species for characterization, and hydratase activities were not reported [55,56]. For CO 2 capture, prominent α-CAs from other eukaryotes were human hCAII, which was produced using bacterial vectors [13], and BovCAII, which was simply purified from bovine erythrocytes [57].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the low porosity, long lateral path lengthening, and low conductance of the intercellular airspace in the maize leaves ( Figure 1 and Figure 2 ), it was, therefore, possible that lateral CO 2 diffusion might be not completely dependent on gaseous diffusion through the intercellular space. Carbonic anhydrase (CA) plays an important role in the initial fixation of CO 2 [ 27 , 28 , 29 , 30 , 31 ]. More importantly, the CA activity in the mesophyll cytoplasm of C 4 plants is higher than that of C 3 plants, while CA in the leaves of C 3 plants is mainly distributed in the chloroplasts [ 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%